Measuring Lean Six Sigma and quality performance for healthcare organizations - Ahmed, Selim; Manaf, Noor Hazilah; Islam, Rafikul (Emerald Publishing Limited, 2018)
Purpose – This study investigates applications of lean six sigma approaches and quality performance in Malaysian hospitals. It identifies five dimensions of lean six sigma conformance (i.e., continuous quality improvement, lean management initiatives, six sigma initiatives, patient safety and teamwork) and quality performance of the hospitals based on demographics such as gender, types of hospital and working experience.